Factor Related to The Anxiety Level of Elderly With Chronic Disease in Kabupaten Sijunjung 2019 - Herlin Silvana; Defriman Djafri; Reni Dayati (Ners Jurnal Keperawatan, 2019)
Anxiety often occurs in the elderly and it can affect the life quality of the elderly. The older a person is, the occurence of anxiety increases. As the number of elderly increases, it is very important to maintain the health of the elderly. If not, it will result in the decreased physical condition, limited mobility, decreased independence, loss of self-confidence and decreased social activity. Knowing and controlling the causative factors of anxiety can be a solution to overcome anxiety in the elderly. This study aimed the factors associated with the anxiety level of the elderly with chronic deseases in Kab. Sijunjung. The design of this research was cross sectional approach and logistic multivariable regressions method. The samples were chosen by a cluster sampling technique with a total of 207 elderly with chronic diseases. The results revealed that factors of income, social support, social activities, and history of trauma had a significant relationship with the anxiety level of the elderly with chronic deseases and social support is the most dominant factor that related to. Thus, it was suggeste to increase the nursing interventions with an approach to the family support and it was focused on improving regular health screening so that the occurence of chronic deseases and anxiety in the elderly could be identified earlier